Impact of the “core” incomes of the regional budgets on the resilience of social-economic subsystems - O. G. Arkadeva; N. V. Berezina (Russian Journal of Economics and Law)
Objective: estimation of the risks of forming the budget incomes of the Russian subjects as a tool for determining the resilience of the regional subsystem.Methods: abstract-logical method, economic-mathematical analysis, coefficient analysis. Results: it was found that for less economically developed regions, the most stable income is gratuitous revenues. It is proved that in accordance with theoretical concepts, risks are determined by the income stability, while in fact, for regions with low and intermediate levels of economic development, the priority role is played by the possibilities of mobilization, which are most obvious for gratuitous revenues. Based on the calculation and evaluation of the income structure indicators, variations of budgets by income and growth rates of the key types of budget income, and using the Federal Treasury data on execution of budgets of the Volga Federal district subjects, it was found that the lowest level of variation is shown by the tax on physical persons incomes; to a lesser extent - the tax levied within the simplified system of taxation, and the tax on property of organizations.Scientific novelty: the authors formulated a hypothesis of a “core” of the subject’s budget revenues, formed with the revenues with a low probability of deviations and high stability, reflected in a single and consistent information base and reflecting the resilience of the region’s economy. It is found that the composition of the “core” income of such regions does not meet the criteria of economic feasibility in the interests of social development and should be altered.Practical significance: the study results can be used in the development of budget and tax policy areas that provide for the decentralization of budget system revenues and the introduction of risk management in the public administration sector.